The impact of Covid-19 Movement Control Order on SMEs’ businesses and survival strategies - Ahmad Raflis Che Omar; Suraiya Ishak; Mohd Abdullah Jusoh (Penerbit Universiti Kebangsaan Malaysia, 2020)
Coronavirus outbreak is the latest world tragedy that have affected all sectors in economy. The lockdown, confinement, limited movement order and social distancing are amongst the preemptive governments’ effort to safeguard the public health. While recognizing the importance of the national order in preventing the immense spread of the virus, the authors contend that there are certain undiscovered impacts of the control order policy on SMEs in Malaysia. The objectives of this article are to scrutinize the implications of the Covid-19 Movement Control Order (MCO) on SMEs businesses and to identify survival strategies based on the owners’ perspectives. The study applies qualitative approach conducted through phone-based interviews with six selected SMEs’ owners during the first phase of control order from March 18, 2020 to March 31, 2020. In summary, the impacts of MCO on SMEs are classified into the operational problems (i.e. operation distruption; supply chain distruption; foresighting the future business direction) and the financial problems (i.e. cash flow imbalance; access to stimulus packages; risk of bankcruptcy). Meanwhile, the major themes of current survival strategies fall under the financial and marketing strategies. The paper recommends few suggestions for future research work, business development agencies and entrepreneurs.